2017
DOI: 10.1093/ofid/ofx264
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Acting Antivirals Improve Access to Care and Cure for Patients With HIV and Chronic HCV Infection

Abstract: BackgroundDirect-acting antivirals (DAA) as curative therapy for hepatitis C virus (HCV) infection offer >95% sustained virologic response (SVR), including in patients with human immunodeficiency virus (HIV) infection. Despite improved safety and efficacy of HCV treatment, challenges remain, including drug-drug interactions between DAA and antiretroviral therapy (ART) and restrictions on access by payers.MethodsWe performed a retrospective cohort study of all HIV/HCV co-infected and HCV mono-infected patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 33 publications
4
52
0
1
Order By: Relevance
“…Surprisingly, recent studies have shown that the uptake rates of DAA treatment remained alarmingly low in the USA and other high-income countries 22–24 32–35. The results from multiple community-based healthcare systems in the USA revealed that, although the treatment rates significantly improved from pre-DAA to post-DAA era, only about one in five HCV-infected patients embarked on DAA therapy 32 33.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, recent studies have shown that the uptake rates of DAA treatment remained alarmingly low in the USA and other high-income countries 22–24 32–35. The results from multiple community-based healthcare systems in the USA revealed that, although the treatment rates significantly improved from pre-DAA to post-DAA era, only about one in five HCV-infected patients embarked on DAA therapy 32 33.…”
Section: Discussionmentioning
confidence: 99%
“…The results from multiple community-based healthcare systems in the USA revealed that, although the treatment rates significantly improved from pre-DAA to post-DAA era, only about one in five HCV-infected patients embarked on DAA therapy 32 33. For HCV/HIV-coinfected patients, the uptake rates of DAA treatment were <20%, with African Americans and Medicaid holders having much lower treatment rates 22 24. In Europe, the rates were similarly low, ranging from <10% to 25%, depending on the countries 23 34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulty parameters varied across the polytomous response categories, with the lowest threshold (b 1 ) indicating the "easiest" (mean -1.489; range -10.527 to -0.109), difficulty progressing as level of stigma endorsement (b 2 ) increased (mean 0.189; range -3.894 to -1.652), and the upper thresholds (b 3 ) all positive (mean 2.146; range 0.842 to 5.785; Table 2). Five items (2,8,12,22,36) were flagged for differential item functioning between patients monoinfected with HCV vs coinfected with HCV/ HIV. Items with low factor loadings and those flagged for differential item functioning were removed, resulting in a 33-item scale (S1 Appendix).…”
Section: Item Response Theory Analysesmentioning
confidence: 99%
“…HCV-associated mortality now exceeds death from 60 other combined notifiable infectious diseases, including human immunodeficiency virus (HIV) infection [2]. Despite national action plans to eliminate HCV infection as a major public health threat by 2030 [5][6][7], fewer than half of HCV-infected persons in the US have been diagnosed or are aware of their infection [8], and treatment uptake remains <15% [9][10][11][12][13], undermining public health efforts.…”
Section: Introductionmentioning
confidence: 99%